THE EFFECT OF SECURITY, EASY OF TRANSACTION ON PURCHASE DECISIONS at JD.ID - Popo Suryana (Faculty of Economic and Business, University of Pasundan, 2022)
The development of the internet facilitates human activities, especially in buying and selling transactions. This study aims to determine the effect of shopping safety and shopping convenience on purchasing decisions at JD.ID for students in Bandung students. The research method used is descriptive and verification with a sample size of 100 respondents. The analysis method uses multiple regression and coefficient of determination. The results of the descriptive analysis show that the shopping security variable is still not safe, the ease of shopping variable is still not easy, and the purchasing decision variable is still not good. The results showed that security and convenience had a positive and significant effect on purchasing decisions of 77.9%. The magnitude of the partial effect of shopping security is 59.76%, ease of shopping is 18.14%.